Gatekhili Mountains, gatekhili State: Fractured Alpine Forest Governance and Post-Soviet Development in the Republic of Georgia - Jesse Quinn (Revue de Géographie Alpine)
While many states at the periphery of the former Soviet Union have pursued decentralization in nearly all areas of governance, this trend is perhaps most notable in natural resource sectors and the effects these reforms have on society. I explore these scalar political, economic, and environmental connections through a qualitative case study of alpine forest governance in the mountains of Georgia. Analyzing a series of thirty-five semi-structured interviews conducted during the summers of 2012 and 2013, I investigate the ways in which state power operates through governance of Georgia’s alpine forests. Like all democracies, the Georgian government oscillates between poles of centralization and decentralization. However, the practices of the Georgian government, as it currently exists through alpine forestry, produces a distinctly fractured (gatekhili in Georgian) form of democracy. The dynamics of the emerging Georgian state as seen through alpine forest governance are informative for understanding the political transition of mountainous post-Soviet states in the 21st century, and contemporary state formation more generally.